Effects of site-directed PEGylation on L-asparaginase thermostability - Cunha, Jheniffer Rabelo (2021)
The enzyme L-asparaginase (ASNase) is broadly applied as a drug to treat acute lymphoblastic leukemia, as well as in the food industry to avoid acrylamide formation in baked and fried food. In the present work, ASNase was covalently attached to polyethylene glycol (PEG) of different molecular weights (ASNase-PEG-5, ASNase-PEG-10, ASNase-PEG-20, and ASNase-PEG-40) at the N-terminal portion (monoPEGylation). Native and PEGylated forms were analyzed regarding thermodynamics and thermostability based on enzyme activity measurements. ASNase (native and PEGylated) presented maximum activity at 40 °C and denaturation followed a first-order kinetics. Based on these results, the activation energy for denaturation (E*d) was estimated and higher values were observed for PEGylated forms compared to the native ASNase, highlighting the ASNase-PEG10 with a 4.24-fold increase (48.85 kJ.mol-1) in comparison to the native form (11.52 kJ.mol-1). The enzymes were evaluated by residual activity over time (21 days) under different storage temperatures (4 and 37 °C) and the PEGylated conjugates remained stable after the 21 days. Thermodynamic parameters like enthalpy (ΔH‡), entropy (ΔS‡) and Gibbs free energy (ΔG‡) of ASNase (native and PEGylated) irreversible denaturation were also investigated. Higher - and positive - values of Gibbs free energy were found for the PEGylated conjugates (61.21 a 63.45 kJ.mol-1), indicating that the process of denaturation was not spontaneous. Enthalpy also was higher for PEGylated conjugates (18.84 a 46.08 kJ.mol-1), demonstrating the protective role of PEGylation. As for entropy, the negative values were more elevated for native ASNase (-0.149 J/mol.K), pointing out that the denaturation process enhanced the randomness and aggregation of the system, which was observed by circular dichroism. Thus, PEGylation proved its potential to increase ASNase thermostability.